Association between osteoporosis, health-related productivity loss and use of hospital services in outpatients of the Brazilian National Health System - Ana Paula Rodrigues Rocha; Bruna Camilo Turi-Lynch; Luana Carolina de Morais; Monique Yndawe Castanho Araujo; Caroline Paula Cristina Palomo; Romulo Araújo Fernandes; Jamile Sanches Codogno (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims To analyze factors associated with osteoporosis among outpatients of the Brazilian National Health System and to identify their association with hospital and labor economic outcomes. Methods Cross-sectional study carried out in the city of Presidente Prudente / SP. The sample consisted of 542 adults of both sexes and aged ≥ 50 years old. The occurrence of osteoporosis, health-related productivity loss, use of hospital services and level of physical activity were assessed using questionnaires. Statistical analysis was composed of chi-square test, binary logistic regression and Mann-Whitney test. The significance level adopted was p-value <0.05. ResultsThe prevalence of osteoporosis was 14.4% (95% CI: 11.4% - 17.3%) and it was associated with female sex (p = 0.001), lower economic status (p-value = 0.036) and obesity (p-value = 0.003). Participants with osteoporosis showed a higher incidence of surgery in the last 12 months (OR = 2.13 [1.04 to 4.35]), productivity loss (OR = 1.91 [1.13 to 3.42]) and disability retirement (OR = 2.03 [1.20 to 3.43]). Over the past 12 months, the sum of direct and indirect economic loss was R$ 1,382,630.00. Conclusion The female sex, lower economic status and obesity were associated with a higher occurrence of osteoporosis, and consequent higher use of hospital services and significant economic losses.